Pattern formation on free surfaces via plastic buckling and periodic folding - Udupa, A.; Viswanathan, K.; Chandrasekar, S. (Europhysics letters, 2020)
Spontaneous formation of surface patterns such as folds and creases is widely observed in engineered systems, such as thin films and machined surfaces, as well as in natural systems such as floral petals and leaves. A recognized route for their formation is via surface elastic instabilities. Here we demonstrate an alternate route for their formation -plastic buckling and folding-that occurs when ductile materials are subject to large-strain (>1) deformation. Using in situ imaging of simple-shear deformation of polypropylene, we delineate the mechanics underlying formation of folds and the resulting surface morphology. The fold pattern shows a single wavelength that scales linearly with the size of the plastic zone. An analytical model predicts onset of the plastic buckling instability and characteristics of the folds. Besides obvious applications for controllably generating surface features over large areas, our results suggest a contributing mechanism for origin of surface roughness in solids.